Durabilidade e transferência de textura superficial via MECT na laminação a frio - Monteiro Junior, Paulo Lourenço (2024)
The present study analyzed the durability and topography transfer of the work roll surface textures during skin pass rolling. Deterministic surface textures were manufactured using the maskless electrochemical texturing (MECT) technique. However, in the skin pass, a noticeable wear on the work roll surface would only be observed after very long periods which would make the tests unfeasible. Thus, the evaluation of the durability of the textures was carried out through tribological reciprocating sliding tests with samples extracted from cold rolling work rolls. Furthermore, the ability of electroless NiP coating to protect textures was evaluated in order to verify its potential to replace the carcinogenic hard chrome coating. The analysis of the texture transfer from the work rolls to the sheets were conducted through pilot scale cold rolling tests. Finally, it was necessary to design, build and validate chambers to texture both the samples for the tribological tests and the work rolls for the rolling tests. The results indicated that the anodic dissolution involved in the texturing of the work roll surface occurred preferentially around the primary carbides. Regarding durability, the friction coefficient in tests on the textured surfaces coated with electroless NiP (TNiP) was lower than that corresponding to surfaces only textured (T) and textured and coated with hard chrome (TCr). Furthermore, the hard chrome and electroless NiP coatings acted to delay the wear of the highest peaks of surfaces textured by MECT method. Finally, rolling tests showed that the work roll surface textured with pockets generated a pillar-textured surface on the sheet. It appears that the mechanism by which the pillars were formed is predominantly reverse extrusion.